Vapor growth of SiC bulk crystals and its challenge of doping - Wellmann, Peter; Müller, Ralf; Queren, Desiree; Sakwe, Aloysius; Pons, Michel (Surface & Coatings Technology, 2006)
The paper reviews the so-called Modified-PVT (M-PVT) technique which combines the state of the art PVT technique for SiC crystal growth with physical and chemical vapor deposition (PVD and CVD) for fine tuning of growth parameters and improved doping. Using this technique, currently the highest aluminum doping levels and lowest resistivity values in p-type bulk SiC were achieved that for the first time meet device fabrication needs. The paper will address fundamentals of the Modified-PVT technique including a comparison of experimental results with numerical modeling of the gas flow. As additional gas feeding helium, helium-aluminum vapor for p-type doping, phosphine for n-type doping and propane for fine tuning of the C/Si gas phase composition will be discussed. So far, the M-PVT concept, i.e. mixture of conventional PVT and fine tuning by PVD/CVD, enables the most flexible doping of SiC single crystals. (c) 2006 Elsevier B.V, All rights reserved.
Keywords: Silicon carbide; crystal growth; doping; modified physical vapor deposition (M-PVT); Al-doping; gas flow; numerical modeling